¿Podía el Preste Juan bloquear o desviar las aguas del Nilo?Fortuna de una leyenda medieval en la Península Ibérica a lo largo de los siglos xvi y xvii - Víctor de Lama de la Cruz (Mélanges de la Casa de Velázquez, 2024)
In the 16th and 17th centuries, the legend that Prester Juan could block or divert the course of the Nile, a power that would cause dire consequences for Egypt, was widely disseminated throughout Spain and Portugal. To understand the origins of this legend in the West, we must go back to the beginning of the 14th century, when it was thought that the dominions of this emperor were in Africa, specifically in Ethiopia. But what western travelers could not suspect is that versions of this legend were already circulating long before the kingdom of Prester John was located in Africa, even before the appearance on the political scene of the 12th century of this priest king who would come to avenge the Christian kingdoms for the failure of the Crusades.